The Snake the Rescuer; The Woman the Avenger: Reversal of Order in Girish Karnad’s Naga-Mandala (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Girish Karnad in his plays makes a dire attempt to create a world where the women would have their due of love, desire and sexuality. Walking beyond the strict rules of the society that has ordained sexual pleasures as the rightful claim of men and that which is a shame when it comes to a woman, Karnad creates an equal ground. The woman protagonist Rani attains the fulfilment of her desires without an iota of guilt and without Nature’s intervention. Nature the primordial had ever been one with human instincts and the urge for sexuality being a prime instinct had never been interfered with. It is civilizations’ bias that had worked on the contrary. Here the power game between the different quarters come to the focus and Nature in the Naga and civilization in the husband face the human in Rani making her victorious.